2017
DOI: 10.1042/bcj20160516
|View full text |Cite
|
Sign up to set email alerts
|

Principles of 60S ribosomal subunit assembly emerging from recent studies in yeast

Abstract: Ribosome biogenesis requires the intertwined processes of folding, modification, and processing of ribosomal RNA, together with binding of ribosomal proteins. In eukaryotic cells, ribosome assembly begins in the nucleolus, continues in the nucleoplasm, and is not completed until after nascent particles are exported to the cytoplasm. The efficiency and fidelity of ribosome biogenesis are facilitated by >200 assembly factors and ~76 different small nucleolar RNAs. The pathway is driven forward by numerous remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 178 publications
1
73
0
4
Order By: Relevance
“…Several remodeling events have been suggested to be required to trigger C2 cleavage, including removal of early assembly factors and assembly of the peptidyl transferase center and polypeptide exit tunnel (recently reviewed in ref. 39). It is unclear how Grc3/Las1 function in concert with other ribosome assembly factors that have been shown to interact with Grc3 and Las1 including the Rix1 complex, Rat1, and Rai1 (4,20).…”
Section: Discussionmentioning
confidence: 99%
“…Several remodeling events have been suggested to be required to trigger C2 cleavage, including removal of early assembly factors and assembly of the peptidyl transferase center and polypeptide exit tunnel (recently reviewed in ref. 39). It is unclear how Grc3/Las1 function in concert with other ribosome assembly factors that have been shown to interact with Grc3 and Las1 including the Rix1 complex, Rat1, and Rai1 (4,20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence gathered over the past 15 years has revealed that LSU assembly occurs within several distinct and successive pre-60S intermediates of partially overlapping composition (Figure 2). The initial steps of LSU assembly remain poorly characterized, but it appears that the formation of the first pre-60S particle depends on termination of transcription and the association of early-binding LSU r-proteins that connect the 5 0 and 3 0 regions of the 27S pre-rRNA [6,11] (Figure 2I). Evidence suggests that rRNA modification may not exclusively occur cotranscriptionally since the presumably earliest pre-60S precursor, isolated via the Npa1 bait protein, still contains C/D-and H/ACA-box snoRNPs [85].…”
Section: Final Maturation Of Pre-40s Particlesmentioning
confidence: 99%
“…These assembly and processing events are tightly coupled and occur within preribosomal particles (see Glossary) that travel, as maturation progresses, from the nucleus across nuclear pore complexes (NPCs) to the cytoplasm, where they are ultimately converted into translation-competent ribosomal subunits [5,[9][10][11][12][13] (Figure 2, Key Figure). Given the gargantuan complexity of this process, it is unsurprising that the assembly of eukaryotic ribosomes strictly requires the assistance of a plethora (>200) of mostly essential ribosome biogenesis factors, which are also called trans-acting or assembly factors [5,14,15].…”
mentioning
confidence: 99%
“… Early co-transcriptional events during eukaryotic ribosome assembly result in the formation of precursors of the small (40S) and large (60S) ribosomal subunits 1 . A multitude of transient assembly factors regulate and chaperone the systematic folding of preribosomal RNA subdomains.…”
mentioning
confidence: 99%